2018
DOI: 10.1001/jamaophthalmol.2017.6135
|View full text |Cite
|
Sign up to set email alerts
|

Association of Changes in Macular Perfusion With Ranibizumab Treatment for Diabetic Macular Edema

Abstract: IMPORTANCE Anti-vascular endothelial growth factor treatment is the first-line therapy in the treatment of center-involving diabetic macular edema. Data on capillary perfusion changes under repeated treatment in a possibly compromised vascular network are limited.OBJECTIVE To evaluate the association of repeated ranibizumab injections on macular perfusion in patients with diabetic macular edema. DESIGN, SETTING, AND PARTICIPANTSThis study analyzed prospectively collected data from the 12-month RESTORE core stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…In addition, repeated anti-VEGF therapy on macular perfusion in patients with DME did not cause treatment-related significant changes in FAZ sizes and capillary loss around the fovea. Patients with DME who had severe ischemia still achieved favorable changes in BCVA and central macular thickness after long-term anti-VEGF therapy [ 6 , 7 ]; thus, anti-VEGF therapy may be an alternative for such patients. Therefore, patients with severe macular ischemia receiving anti-VEFG therapy should be individualized, and they need a comprehensive assessment of possible risks and closer follow-up to prevent the worsening of ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, repeated anti-VEGF therapy on macular perfusion in patients with DME did not cause treatment-related significant changes in FAZ sizes and capillary loss around the fovea. Patients with DME who had severe ischemia still achieved favorable changes in BCVA and central macular thickness after long-term anti-VEGF therapy [ 6 , 7 ]; thus, anti-VEGF therapy may be an alternative for such patients. Therefore, patients with severe macular ischemia receiving anti-VEFG therapy should be individualized, and they need a comprehensive assessment of possible risks and closer follow-up to prevent the worsening of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, some clinical studies suggested that blocking VEGF might be harmful to retinal vascular integrity, especially in patients with preexisting retinal ischemia; in these patients, anti-VEGF therapy aggravated retinal ischemia because retinal nonperfusion (RNP) areas enlarged after anti-VEGF therapy [5,6]. However, increasing studies have shown that retinal ischemia does not worsen after anti-VEFG therapy but has no retinal reperfusion in the preexisted RNP areas [7][8][9]. After anti-VEGF treatment, the proportion of patients with ≥2-step DR severity score improvement is greater in patients with MNP at baseline [10].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of retinal nonperfusion assessed by fluorescein angiography was found to be decreased 1 month after treatment [ 35 ] and reported unchanged in other studies after 6–12 month [ 33 , 35 ]. No significant differences were reported in parafoveal vascular densities, FAZ, vascular caliber changes or reperfusion before and up to 12 month after anti-VEGF therapy [ 28 32 ]. However, other authors demonstrated transient changes in vascular parameters, namely FAZ enlargement and retinal arteriolar vasoconstriction 4–6 weeks after anti-VEGF injections [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, repeated anti-VEGF therapy on macular perfusion in patients with DME did not cause treatment-related significant changes in FAZ sizes and capillary loss around the fovea. Patients with DME who had severe ischemia still achieved favorable changes in BCVA and central macular thickness after long-term anti-VEGF therapy [7,17]; thus, anti-VEGF therapy may be an alternative for such patients. Therefore, patients with severe macular ischemia receiving anti-VEFG therapy should be individualized, and they need a comprehensive assessment of possible risks and closer follow-up to prevent the worsening of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, some clinical studies suggested that blocking VEGF might be harmful to retinal vascular integrity, especially in patients with preexisting retinal ischemia; in these patients, anti-VEGF therapy aggravated retinal ischemia because retinal nonperfusion (RNP) areas enlarged after anti-VEGF therapy [5,6]. However, increasing studies have shown that retinal ischemia does not worsen after anti-VEFG therapy but has no retinal reperfusion in the preexisted RNP areas [7][8][9]. Meanwhile, few studies indicated that anti-VEGF therapy could reduce RNP progression.…”
Section: Introductionmentioning
confidence: 99%